GENETIC VARIABILITY, HERITABILITY AND GENETIC ADVANCE FOR YIELD AND ITS ATTRIBUTES IN POTATO (SOLANUM TUBEROSUM L.) - BARIK, SMITA BALA; VERMA, SATISH K.; NANDA, H.C.; TAMRAKAR, S. K (Annals of Agricultural Research, 2014)
Forty four genotypes were evaluated for thirteen characters. Characters marketable yield, total tuber yield and number of tubers per plant had higher genotypic and phenotypic coefficient of variation, whereas the moderate magnitude of PCV and GCV was observed for per cent emergence, fresh weight of shoots/plant and plant height. High heritability estimates for the characters fresh weight of shoots/plant, harvest index, dry weight of tubers/plant, per cent emergence, total number of leaves/plan, fresh weight of tubers/plant total tuber yield/plot, plant height and dry weight of shoots/plant. High genetic advance as percentage of mean was obtained for characters namely dry weight tubers/plant and total tuber yield/plot. High heritability coupled with high genetic advance was recorded for the traits viz. dry weight of tubers and total tuber yield/plot. Result reveal that the genotypic coefficient of variation, high heritability and genetic advance may be exploited in further breeding programme.